Decisions of the Federal Constitutional Court: Volume 6: General right of personality - Federal Constitutional Court (Nomos Verlagsgesellschaft mbH & Co. KG, 2022)
Curated, translated and edited by the Court’s translation unit in collaboration with the Justices, the sixth volume of this English-language series is dedicated to one of the cornerstones of German fundamental rights architecture: the general right of personality. Following a thematic introduction by Justices of the Court, this volume presents 45 leading cases that map the constitutional protection of self-determination, identity and privacy from the early foundations to recent decisions on the right to be forgotten, assisted suicide and the state’s surveillance powers abroad. For the international legal community, scholars and anyone interested in comparative law, this book constitutes an invaluable guide to decades of constitutional case-law in Germany.